2013
DOI: 10.1016/j.socscimed.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Eye of the beholder? Maternal mental health and the quality of infant sleep

Abstract: Transactional models of parenting and infant sleep call attention to bidirectional associations among parenting, the biosocial environment, and infant sleep behaviors. Although night waking and bedtime fussing are normative during infancy and early childhood, they can be challenging for parents. The current study, conducted in the United States between 2003 and 2009, examined concurrent and longitudinal associations between maternal mental health and infant sleep during the first year. Concurrent associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 48 publications
(68 reference statements)
5
37
0
1
Order By: Relevance
“…Previous research has repeatedly revealed an association between infant sleep problems and maternal depression and distress. [21][22][23][24][25] Our findings indicate that multiple moderate-tosevere infant regulatory problems are associated with greatly increased rates of maternal distress, with approximately one-third of mothers with infants who are severely unsettled reporting distress in the clinical range. Interventions that are targeted at the mother-infant dyad rather than the infant regulatory problem in isolation may be the most appropriate for these families.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has repeatedly revealed an association between infant sleep problems and maternal depression and distress. [21][22][23][24][25] Our findings indicate that multiple moderate-tosevere infant regulatory problems are associated with greatly increased rates of maternal distress, with approximately one-third of mothers with infants who are severely unsettled reporting distress in the clinical range. Interventions that are targeted at the mother-infant dyad rather than the infant regulatory problem in isolation may be the most appropriate for these families.…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum depression when the child is 5 months old is associated with more infant nighttime awakenings at 9 months old [15]. Maternal depression and anxiety when the child is 6 or 12 months old is associated with concurrent infant sleep problems, and maternal anxiety when the child is 6 months old is associated with more crying at bedtime 6 months later [16]. The association of maternal depression and infants’ sleep among 1- to 24-month-old infants may come about because mothers who are depressed or worried about their infants’ nighttime needs spend more time with their infants during the night, and maternal nighttime presence predicts more infant awakenings.…”
Section: Family Structure Household Factors and Sleepmentioning
confidence: 99%
“…Concern has been raised also about how infant nightwakings may affect maternal well-being, especially levels of maternal depression (Bayer, Hiscock, Hampton, & Wake, 2007;Goldberg et al, 2013;Karraker & Young, 2007). Nightwakings, however, may not be the strongest contributor to postnatal depression.…”
Section: Current Researchmentioning
confidence: 99%